Mapping and Preliminary Analysis of ABORTED MICROSPORES (AMS) as the Candidate Gene Underlying the Male Sterility (MS-5) Mutant in Melon (Cucumis melo L.) - Sheng, Yunyan; Wang, Yudan; Jiao, Shiqi; Jin, Yazhong; Ji, Peng; Luan, Feishi (Frontiers in Plant Science, 2017)
Melon is an important agricultural and economic vegetable crop worldwide. The genetic male sterility mutant (ms-5) has a recessive nuclear gene that controls the male sterility germplasm. Male sterility could reduce the cost of F1 seed production in melon, but heterozygous fertile plants should be removed before pollination. In this study, bulked segregant analysis (BSA) combined with specific length amplified fragment sequencing (SLAF-seq) was applied to map the single nuclear male sterility recessive gene. A 30-kb candidate region on chromosome 9 located on scaffold 000048 and spanning 2,522,791 to 2,555,104 bp was identified and further confirmed by cleavage amplified polymorphic sequence (CAPS) markers based on parental line resequencing data and classical mapping of 252 F2 individuals. Gene prediction indicated that 6 annotated genes are present in the 30-kb candidate region. Quantitative RT-PCR revealed significant differences in the expression level of the LOC103498166 ABORTED MICROSPORES (AMS) gene in male-sterile lines (ms-5) and male-fertile (HM1-1) lines during the 2-mm (tetrad) and 5-mm (the first pollen mitosis) periods, and negative regulation of the AMS candidate gene transcription factor was also detected. Sequencing and cluster analysis of the AMS transcription factor revealed five single-nucleotide polymorphisms (SNPs) between the parental lines. The data presented herein suggest that the AMS transcription factor is a possible candidate gene for single nuclear male sterility in melon. The results of this study will help breeders to identify male-sterile and -fertile plants at seeding as marker-assisted selection (MAS) methods, which would reduce the cost of seed production and improve the use of male-sterile lines in melon.